Seasonal Analysis of Taxonomic and Functional Diversity of Poneromorph Ant Assemblages in the Amazon Forest - Pereira, L. P. C.; Almeida, F. S.; Vargas, A. B.; Araujo, M. S. [UNESP]; Mayhe-Nunes, A. J.; Queiroz, J. M. (Univ Estadual Feira Santana, 2016)
The present study aimed at assessing the effects of climate seasonality on poneromorph ants in the Brazilian Amazon, by studying variations in composition, richness, and taxonomic and functional diversity. The study was carried out in the Tapirape-Aquiri National Forest, southeastern Para State. We collected poneromorph ants in three areas of native forest with pitfall traps and sardine baits on the ground and vegetation, in two dry and rainy seasons. We collected 46 species of poneromorph ants, which belong to two subfamilies and eleven genera. The species composition, richness and taxonomic diversity did not vary significantly between seasons. There was no significant difference in the frequency of species of functional groups between dry and rainy seasons. There was no significant difference in the average richness and average diversity of functional groups between the dry and rainy seasons. In our study we found no seasonal differences in composition, taxonomic and functional richness and diversity of poneromorph ants in the Amazon, which is useful for future studies that aim at using those ants as bioindicators. In addition, the identification of the species made in the present study has special relevance as it contributes to advance the knowledge of poneromorph ant diversity in the Amazon.
Keywords: Biodiversity; Formicidae; protected area